Promising Effect of High Dose Ambroxol Treatment on Neurocognition and Motor Development in a Patient With Neuropathic Gaucher Disease 2 - Aries, Charlotte; Lohmöller, Benjamin; Tiede, Stephan; Täuber, Karolin; Hartmann, Guido; Rudolph, Cornelia; Muschol, Nicole (Frontiers in Neurology, 2022)
Gaucher Disease (GD) 2 is a rare inherited lysosomal disorder. Early-onset and rapid progression of neurovisceral symptoms lead to fatal outcome in early childhood. Treatment is symptomatic, a curative therapy is currently not available. This prospective study describes the clinical and biochemical outcome of a GD 2 patient treated with high dose ambroxol from the age of 4 months. Due to progressive hepatosplenomegaly additional enzyme replacement therapy was required 1 year after ambroxol monotherapy was initiated. Detailed clinical follow-up data demonstrated an age-appropriate neurocognitive and motor development but no clear benefit on peripheral organs. Glucosylsphingosine (Lyso-GL1) in cerebrospinal fluid decreased remarkably compared to pre-treatment, whereas Lyso-GL1 and chitotriosidase in blood increased. Ambroxol treatment of patient fibroblasts revealed a significant increase in β-glucocerebrosidase activity in vitro. To our knowledge, this is the first report of a GD 2 patient with age-appropriate cognitive and motor development at 3 years of age. Combination of high dose ambroxol with ERT proved to be a successful approach to manage both visceral and neurological manifestations.